Ответ:-1;1;1/2;3
Объяснение:
2x^4-5X^3-5X^2+5x+3=0
2x^4-2x^3-3x^3+3x^2-8X^2+8x-3x+3=0
2X^3(x-1)-3x^2(x-1)-8x(x-1)-3(x-1)=0
(x-1)(2x^3-3x^2-8x-3)=0
(x-1)(2x^3+2x^2-5x^2-5x-3x-3)=0
(x-1)[(2x^2(x+1)-5x(x+1)-3(x+1)]=0
(x-1)(x+1)(2x^2-5x-3)=0
(x-1)(x+1)(2X^2+x-6x-3)=0
(x-1)(x+1)[(x(2x+1)-3(2x+1)]=0
(x-1)(x+1)(2x+1)(x-3)=0⇒ x=1; х=-1; х=-1/2; х=3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:-1;1;1/2;3
Объяснение:
2x^4-5X^3-5X^2+5x+3=0
2x^4-2x^3-3x^3+3x^2-8X^2+8x-3x+3=0
2X^3(x-1)-3x^2(x-1)-8x(x-1)-3(x-1)=0
(x-1)(2x^3-3x^2-8x-3)=0
(x-1)(2x^3+2x^2-5x^2-5x-3x-3)=0
(x-1)[(2x^2(x+1)-5x(x+1)-3(x+1)]=0
(x-1)(x+1)(2x^2-5x-3)=0
(x-1)(x+1)(2X^2+x-6x-3)=0
(x-1)(x+1)[(x(2x+1)-3(2x+1)]=0
(x-1)(x+1)(2x+1)(x-3)=0⇒ x=1; х=-1; х=-1/2; х=3